An interrelation between the adsorption-desorption and surface diffusion mechanisms under concentration decomposition of an open submonoatomic overlayer - Feldman, E.P.; Gumennyk, K.V.; Stefanovich, L.I.; Terekhova, Yu.V. (Functional Materials, 2012)
Thermodynamic and kinetic formation of a sub-monoatomic adsorbed film under it precipitation from the atmosphere of vapor phase upon atomically smooth single-crystal surface in and subjected to rapid quenching is studied. Early and late time asymptotics for the coverage dispersion as well as the scaling behavior of the average domain size is founded. In considered case average size of inhomogeneity on the late stage increase of root law, but thickness of transition region between enriched and depleted parts of film decrease of inverse root law by time. Розглянуто термодинаміку та кінетику формування субмоноатомної адсорбованої плівки при осаджуванні її з парової фази шляхом швидкого загартування на атомарно-гладку монокристалічну поверхню. Визначено як ранні, так і пізні часові асимптотики щодо дисперсії покриття, а також скейлінгову поведінку середнього доменного розміру. Показано, що у розглянутому випадку середній розмір неоднорідностей на пізніх стадіях зростає за кореневим законом, а товщина перехідної області між збагаченими та збідненими ділянками плівки зменшується з часом за законом оберненого кореня. Рассмотрена термодинамика и кинетика формирования субмоноатомной адсорбированной пленки при осаждении ее из паровой фазы путем быстрой закалки на атомарно-гладкую монокристаллическую поверхность. Определены ранние и поздние временные асимптотики для дисперсии покрытия, а также скейлинговое поведение среднего доменного размера. Показано, что в рассмотренном случае средний размер неоднородностей на больших временах растет по корневому закону, а толщина переходной области между обогащенными и обедненными участками пленки убывает со временем по закону обратного корня.